Efectos que tiene el contenido de la programación de canal uno en el comportamiento de las adolescentes de la pre cooperativa Jaime Roldós Aguilera - Godoy Quiñonez, Rosa Paola (2016)
In this research and field work will be done an analysis of the program schedule of Channel One and how it influences adolescent Pre-Cooperative Jaime Roldós Aguilera. While it is true, television is taken as an educational medium, questioned at times as an example of decay for people especially children, adolescents and young people, as the see excess programs that do not have their own meaning or values may cause serious problems in the behavior of the same and it is there, experts say where the rebellion originated, its change in the way of acting, thinking, dress and disrespect toward their elders. For all the above and seeing this problem that afflicts today to Ecuador has proposed to develop this research will provide a journey through the history of television and domestic production in order to determine what are the programs that cause these problems affecting home and therefore to society. To make the project has been chosen as the main tool polls and surveys the inhabitants of the Pre-Cooperative Jaime Roldós Aguilera, and proceeded to conduct interviews with professionals in the media, in order to assess the possible influence TV programs have in relation to knowledge and behavior of adolescents…..